THE DEPENDENCE OF THE WEAR RESISTANCE OF THE COMPOSITE COATING PRECIPITATED ON THE DISPERSION OF ITS FILLER - Мельник, Петро Іванович; Кіндрачук, Мирослав Васильович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
Research shows that the process of wearout TCT is conducted on nickeliferous basis at the dry friction of sliding. Factory configured that depending on the size of carbidic phase of TіС and diffusive chrome-plating, coming from the understanding of transformation energy of flowage in the area of contact to energy of distributions in the area of friction which conduces to painting of hard phase.